Evaluation of multiple criteria quality of mathematics learning objects in eQNet project - Sėrikovienė, Silvija; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2010)
The paper is aimed to analyse the application of several scientific approaches, methods, and principles for evaluation of quality of digital learning objects (LOs) for Mathematics subject. The authors analyse the following approaches to minimise subjectivity level in expert evaluation of LOs quality, namely: (1) principles of multiple criteria decision analysis for identification of quality criteria, (2) technological quality criteria classification principle, (3) fuzzy group decision making theory toobtain evaluation measures, (4) normalisation requirement for criteria weights, and (5) scalarisation method for LOs quality evaluation. The applied approaches have been used practically for evaluation of LOs while implementing European Lifelong Learning programme’s eQNet project in Lithuanian comprehensive schools in winter and spring 2010.
Keywords: learning object; multiple criteria decision analysis; expert evaluation; quality criteria